Penerapan Game Based Learning Berbasis untuk Meningkatkan Motivasi Belajar Anak Panti Asuhan - Keysha Alisya Putri Sonatha; Khalida Nurluthfi; Suci Rahma Putri; Astri Anggraini Hapsara Wibowo (Lembaga Yasin AlSys, 2026)
Low learning motivation among children living in orphanages is an important issue because it is characterized by a tendency to become easily bored, lack consistency in completing tasks, become easily distracted, and have low self-confidence. This condition is influenced by limited caregiver attention and the suboptimal implementation of a structured disciplinary system in the orphanage environment. This study aims to examine the effectiveness of an educational game-based intervention in increasing children’s learning motivation at Panti Asuhan X, West Jakarta. This study used a pretest-posttest design involving 8 children, consisting of 7 boys and 1 girl aged 6–13 years. The game-based learning intervention was developed based on Self-Determination Theory (SDT) through four games, namely “Human Body Monopoly,” “Flash Cards,” “UNO Stacko for Question Cards,” and “Cup Pyramid Quiz Game.” Data were collected using the Indonesian translated version of the Elementary School Motivation Scale (ESMS), which covers the dimensions of reading, writing, and completing tasks, then analyzed descriptively using IBM SPSS Statistics and Microsoft Excel. The results show an increase in the average learning motivation across the three dimensions after the intervention. The reading dimension increased from 33.00% to 34.50%, the writing dimension increased from 30.63% to 33.38%, and the highest increase occurred in the task-completion dimension, from 27.75% to 33.50%. The conclusion of the study affirms that educational game-based learning has the potential to be effective in increasing the learning motivation of children in orphanages. The implications of this study provide practical contributions for caregivers, educators, and social institutions in designing learning activities that are enjoyable, participatory, and aligned with children’s psychological needs.